Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE Varnished and Enamelled Woodwork, Paintwork, and Varnished Paper. — Dust first, then use a soft cloth wrung out of soapy water. Rinse with one dipped in cold. Wash from bottom upwards — not up and down. Nursery walls should be painted or varnished so that they can be washed easily with soap and water. Steps should be washed with soap and hot water and rinsed with warm water. The old-fashioned, laborious way of smearing steps with bathbrick is abandoned by the modern housewife. Carpeted Stairs. — Wipe the painted edges once a week with a cloth wrung out of soapy water. When the carpet is up, give the woodwork underneath a good scrubbing with hot water and disinfectant soap. Windows and Sashes. — Clean the windows with a leather wrung out of warm water. Dry with a cloth that is not fluffy. Polish with paper. Wash the sashes as you would paintwork. Carpets are most easily and effectively cleaned with the vacuum cleaner, various models of which are now on the market at very reasonable prices. Germs are carried on dust particles, and in the process of “doing out” a room by the old-fashioned method of brushing and sweeping these particles pass into the air to be breathed into the nostrils and lungs. With the cleaner at work the dust does not fly into the air as it does with the old-fashioned carpet-brushing method, but is entrapped in the dust-proof bag with which the cleaner is equipped. This modern method of dust-removing instead of dust-distributing is the ideal of healthy home practice. Some of the most modern homes are now fitted with a central vacuum system. If this most Page Six 177/5/8/1